The Value-Added Tax (VAT) administration benchmarking: A case study of Western European countries - Shapovalova, Alla; Demianyshyna, Olesia; Kudlaieva, Nataliia; Plekan, Mariia; Skrypnyk, Svitlana (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Given the instability of the economic environment, governments of even highly developed countries are facing the question of implementing changes to the VAT administration system. The study aims to analyse the specifics of VAT administration and accounting procedures in Western European countries based on the formation of criteria for the optimal administration model. The resulting criteria for the optimality of the VAT administration and accounting system serve as a basis for implementing changes to the current VAT administration models in the countries where this tax is not a key source of budget revenue yet, and for the countries that strive to increase the stability and volume of VAT revenues.